Swiss monetary history since the early 19th century - Baltensperger, Ernst 1942-; Kugler, Peter (Cambridge University Press, 2017)
This book describes the remarkable path which led to the Swiss Franc becoming the strong international currency that it is today. Ernst Baltensperger and Peter Kugler use Swiss monetary history to provide valuable insights into a number of issues concerning the organization and development of monetary institutions and currency that shaped the structure of financial markets and affected the economic course of a country in important ways. They investigate a number of topics, including the functioning of a world without a central bank, the role of competition and monopoly in money and banking, the functioning of monetary unions, monetary policy of small open economies under fixed and flexible exchange rates, the stability of money demand and supply under different monetary regimes, and the monetary and macroeconomic effects of Swiss Banking and Finance. Swiss Monetary History since the Early 19th Century illustrates the value of monetary history for understanding financial markets and macroeconomics today
Title from publisher's bibliographic system (viewed on 11 Aug 2017)
Keywords: Geschichte; Money / Switzerland / History; Monetary policy / Switzerland / History; Finance / Switzerland / History; Schweiz